Primary Prevention of Cardiovascular Risk in Octogenarians by Risk Factors Control - Palmiero, Pasquale; Zito, Annapaola; Maiello, Maria; Cecere, Annagrazia; Mattioli, Anna V.; Pedrinelli, Roberto; Scicchitano, Pietro; Ciccone, Marco Matteo (Current Hypertension Reviews, 2019)
Primary prevention of cardiovascular events in older adults is a relevant problem, due to lack of evidence for safe and efficacious therapy, its costs and elderly quality of life, Italy’s aging population is constantly increasing, so cardiovascular disease (CVD) primary prevention in the elderly is a prime objective. Life expectancy has dramatically increased over the last 2 decades, the proportion of individuals aged 80 years and older has grown rapidly in Europe and the United States, but cost / effective ratio of CVD prevention through risk factors control is debated. It is therefore important to implement cardiovascular risk factors estimation in the elderly to maximize the quality of life of patients and to lengthen their healthy life expectancy, choosing the better treatment for each patient sharing the choice with himself when it is possible, always remembering that elderly patients often have multiple co-morbidities that require a high number of concurrent medications; this may increase the risk for drug-drug interactions, thereby reducing the potential benefits of CVD prevention therapy. Nevertheless, CVD is not an inevitable concomitant of aging. Sometimes, autopsy in the elderly reveals atheroma-free coronary arteries, a normal-sized heart and unscarred valves. All primary prevention strategy decisions should consider estimated life expectancy and overall function and not just the cardiovascular event risks, magnitude and time to benefit or harm, potentially altered adverse effect profiles, and informed patient preferences. CVD primary prevention needs to be more implemented in the elderly, this might contribute to improve health status and quality of life in this growing population if correctly performed.
Keywords: Primary prevention